2020
DOI: 10.1111/codi.15354
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic multicentre factorial randomized controlled trial testing measures to reduce surgical site infection in low‐ and middle‐income countries: study protocol of the FALCON trial

Abstract: Aim Surgical site infection (SSI) is the commonest postoperative complication worldwide, representing a major burden for patients and health systems. Rates of SSI are significantly higher in low‐ and middle‐income countries (LMICs) but there is little high‐quality evidence on interventions to prevent SSI in LMICs. Method FALCON is a pragmatic, multicentre, 2 x 2 factorial, stratified randomized controlled trial, with an internal feasibility study, which will address the need for evidence on measures to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In this ongoing COVID-19 pandemic, when most of the clinical work has been reduced to only essential services in majority of surgical units, the role of multicentric studies cannot be over emphasized. Availability of broadband Internet connections and ease of online collaborations have brought the feasibility of multicentric trials to everyone’s doorstep [ 23 ]. An additional advantage of this is the possibility of increasing participation by smaller hospitals from tier 2 and tier 3 cities.…”
Section: Discussionmentioning
confidence: 99%
“…In this ongoing COVID-19 pandemic, when most of the clinical work has been reduced to only essential services in majority of surgical units, the role of multicentric studies cannot be over emphasized. Availability of broadband Internet connections and ease of online collaborations have brought the feasibility of multicentric trials to everyone’s doorstep [ 23 ]. An additional advantage of this is the possibility of increasing participation by smaller hospitals from tier 2 and tier 3 cities.…”
Section: Discussionmentioning
confidence: 99%
“…FALCON is a stratified, pragmatic, multi-centre, 2 × 2 factorial trial testing two measures (skin preparation and antimicrobial sutures) to reduce superficial or deep skin infection following abdominal surgery in seven low-and middle-income countries (NCT03700749) [8]. ChEETAh is a cluster randomised trial evaluating whether the practice of using separate sterile gloves and instruments to close wounds at the end of surgery compared to current routine hospital practice can reduce surgical site infection at 30 days after abdominal surgery [26].…”
Section: Host Trialsmentioning
confidence: 99%
“…This protocol is reported with reference to recommendations from the Global Health Network for qualitative research in LMICs and Consolidated criteria for reporting qualitative research (COREQ) framework [27,28], recommendations for best practices in a mixed-methods adaptation of outcome measures [29], and STARD guidelines for diagnostic test accuracy studies [30]. The protocols for the two host trials are reported elsewhere [8,26]. This SWAT protocol has been pre-registered on the MRC Hubs for Trial Methodology Research Study Within a Trial database [25] (Queen's University Belfast) (SWAT ID:126).…”
Section: Reporting and Registrationmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Depending on the degree of intraoperative contamination, baseline patient risk and other infection control measures, as many as 50% of patients can suffer surgical wound infections within the 30-days after an operation. 2 As a result, SSI has been the focus of several recent global initiatives including randomised controlled trials of health technologies, 3 quality improvement bundle studies, [4][5][6] and prospective cohort studies. 2,7 Regimens of antibiotic prophylaxis are a key component in the SSI prevention pathway.…”
Section: Editorialmentioning
confidence: 99%